A Practical Approach to Teaching Mexican Political Cabaret - Alzate, Gastón; Marín, Paola (Latin American Theatre Review, 2017)
This article presents a practical approach to teaching Mexican political cabaret theatre in the US. It starts with a brief overview of the reasons why the movement begun to flourish in the 80s, as well as its connections to tent theatre (carpa), and musical revue theatre from the early 20th century. While it is impossible to state a single approach to the teaching and practice of contemporary Mexican cabaret—as multiple actors and troupes have developed their own approaches—their common traits are indicated here. The starting point is a workshop the authors took with Nora Huerta and Cecilia Stores at Mexico’s National Center for the Arts in August 2015. Ms. Huerta and Ms. Stores are actresses/directors belonging to the well-known Las Reinas Chulas (Cute Little Queens) cabaret troupe. The article ends by offering examples of sketches dealing with US political hegemony by significant Mexican cabaret artists. These may be of interest for US artists and faculty members interested in teaching Mexican political cabaret in particular and Latin American theatre in general.